Mechanisms and kinetics of (de-)protection of soil organic carbon in earthworm casts in a tropical environment. (July 2022) - Puche, N.; Rumpel, C.; Le Mer, G.; Jouquet, P.; Mazurier, A.; Caner, L.; Garnier, P.; Tran, T.M.; Bottinelli, N.
Abstract: Earthworms have potential to stabilize soil organic carbon (SOC), but the biophysical controls on SOC dynamics in earthworm casts and the SOC residence time in casts is poorly known. To this end, we aimed to investigate (1) the kinetics of SOC (de-) protection in earthworm casts deposited in a tropical environment and (2) changes in the spatial relationships between fresh particulate organic matter (POM) and pore architecture within casts. Our experimental approach was to espose casts produced by the anecic earthworm Amynthas adexilis to tropical temperature and rainfall by placing them in a woodland in northern Vietnam. For 400 d, we monitored the dynamics of cast microstructures using X-ray micro-computed tomography and compared them to those of the surrounding soil aggregates (control). We also measured potential CO2 emissions of the same samples in a laboratory incubation. As expected, recently egested casts had higher SOC (1.9-fold) and POM volumes (7-fold) than aggregates, whereas their total imaged porosity was 4 times less. The SOC of casts was more labile than SOC of aggregates, as casts had 3 times more potentially mineralizable SOC. By 72 d of exposure to field conditions, the casts and aggregates had similar potential SOC mineralization, indicating that they had developed a similar level of SOC protection. Temporal changes in SOC mineralization rates were related to variations in POM volume, particularly those connected to the outside of the cast. After 400 d of exposure, casts had still greater POM volumes (2.5-fold) and higher SOC contents (1.6-fold) but similar total imaged porosity and SOC stability as aggregates. In conclusion, these results clearly indicated the direct involvement of earthworms in SOC stabilization through their impact on POM and pore spatial arrangements, which may have led to prolonged SOC sequestration for > 400 d. Highlights: Soil organic C protection in fresh earthworm casts became apparent after 72 d. Stabilization occurred within pores not connected to the outside of aggregates. Physical protection led to soil organic C sequestration in casts for > 400 d.